Economic growth and social welfare operationalising normative social choice theory - Clarke, Matthew; Islam, Sardar M. N., 1950- (Contributions to economic analysis ;, 2004)
This book studies the relationships between economic growth and social welfare and the policy implications of these relationships for development. Understanding the relationships between economic growth and social welfare is an enduring issue within contemporary development economics and welfare economics. These relationships are analysed in this book by operationalising normative social choice theory. Normative social choice theory is an appropriate approach as it explicitly incorporates society's preferences, values and choices in determining how social welfare should be defined and measured. Two approaches, aggregate and hierarchical, are developed and empirically applied to Thailand for a twenty-five year period 1975-1999. This book concludes that in terms of social welfare, economic growth cannot always be assumed desirable. What is needed is social welfare enhancing economic growth. A review of the policy implications of this finding is also undertaken.